Is pre-eclampsia really increased in women with type 1 diabetes?. (18th April 2012) - Maresh, MJA; Holmes, VA; Patterson, CC; Pearson, DWM; Walker, JD; Young, IS; McCance, DR
Abstract : Pregnancy with type 1 diabetes is considered to have a high incidence of pre-eclampsia (PET), but these women often have hypertension or proteinuria at <20 weeks gestation confusing the diagnosis. The DAPIT study randomised 762 women with type 1 diabetes to vitamin C and E supplementation, to investigate if this reduced the incidence of PET. As no significant effect was found both groups were combined allowing analysis of hypertensive disorders in a large cohort. Before pregnancy, previous hypertension was noted in 25% of women who developed PET, 13% of women who developed gestational hypertension (GHT) and 10% who had neither (p <0.001). By 20 weeks 32% of women had hypertension, proteinuria or both and 29% were subsequently classified as having PET in contrast to only 12% who had no problem <20 weeks (p <0.0001). However, of those who were classified as having PET, 56% had evidence of hypertensive or renal impairment <20 weeks compared to 24% who had no subsequent hypertensive problem (p <0.0001). While liver enzymes and serum urate were significantly elevated in the PET group the results were similar whether or not there was a problem <20 weeks. However thrombocytopenia occurred more in the PET group who only had a problem >20 weeks. Birthweight <5 th and <90 th centile was significantly greater in the PET group, but significantly more in those with a problem<20 weeks. In conclusion not all diabetic women classified as having PET appear to have the condition but further markers are required to differentiate.